The Role of the Secretary of a Parity Committee - Gérin, Raymond (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1952)
In this article, the author wishes to show the important role that the secretary of a parity committee, by his functions, must play. These functions vary from one parity committee to another, but generally are those determined by the Collective Agreement Act and suggested by the sample regulations recommended by the Department of Labour. In addition to these duties, the secretary takes part in the conduct and orientation of the parity committee, not only as administrator but also as a specialist in a sector of labour relations possessing an awakened social conscience. In order to act with efficiency and durability, he must be particularly rich in qualities and resources and thus be able to assure the continuation and orientation of this organization with which he is entrusted.